Investigation of the role of the BcI-2 family proteins in Ras-induced transformation - Elgendy, Mohamed (Trinity College (Dublin, Ireland). Department of Genetics, 2011)
RAS is a proto-oncogene that is found mutated in 25% of human tumours. Deregulated Ras expression is typically insufficient to transform cells as it triggers anti-proliferative responses that altogether limit tumorigenesis. Cooperating mutations are thus required to allow cells to evade such responses and to proceed to full transformation. Mutational activation of Ras has been shown to induce cell cycle arrest and senescence.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.